2021
DOI: 10.1101/2021.03.29.437611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproducible Coactivation Patterns of Functional Brain Networks Reveal the Aberrant Dynamic State Transition in Schizophrenia

Abstract: It is well documented that massive dynamic information is contained in the resting-state fMRI. Recent studies have identified recurring states dominated by similar coactivation patterns (CAP) and revealed their temporal dynamics. However, the reproducibility and generalizability of the CAP analysis is unclear. To address this question, the effects of methodological pipelines on CAP are comprehensively evaluated in this study, including preprocessing, network construction, cluster number and three independent c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 76 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…It also has a better temporal resolution and does not require predefined parameters such as window length, as the analytical unit of CAP analysis is a single volume. Besides, our previous study has shown the robustness of CAPs across several technique flexibilities and independent cohorts, and reproducible alterations were also obtained between schizophrenia patients and healthy controls (Yang et al 2021). Recently, CAP analysis has been used to study the altered brain dynamics in patients with depression (Kaiser et al 2019) and Alzheimer’s disease (Ma et al 2020).…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…It also has a better temporal resolution and does not require predefined parameters such as window length, as the analytical unit of CAP analysis is a single volume. Besides, our previous study has shown the robustness of CAPs across several technique flexibilities and independent cohorts, and reproducible alterations were also obtained between schizophrenia patients and healthy controls (Yang et al 2021). Recently, CAP analysis has been used to study the altered brain dynamics in patients with depression (Kaiser et al 2019) and Alzheimer’s disease (Ma et al 2020).…”
Section: Introductionmentioning
confidence: 60%
“…Similar to our previous study, the mean BOLD time series was extracted from 408 ROIs separately (Yang et al 2021), which includes 400 cortical regions (Schaefer et al 2018) and 8 subcortical regions (bilateral caudate nucleus, putamen, globus pallidus and amygdala) from the AAL template (Tzourio-Mazoyer et al 2002). The 400 cortical regions belong to 7 networks, including the visual network (VN), somatomotor network (SMN), dorsal attention network (DAN), ventral attention network (VAN), limbic network, fronto-parietal network (FPN) and default mode network (DMN).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations